The experience of neoliberal education - Urciuoli, Bonnie, 1949- (Higher education in critical perspective, 2018)
"The college experience is increasingly positioned to demonstrate its value as a worthwhile return on investment. Specific, definable activities, such as research experience, first-year experience, and experiential learning, are marketed as delivering precise skill sets in the form of an individual educational package. Through ethnography-based analysis, the contributors to this volume explore how these commodified 'experiences' have turned students into consumers and given them the illusion that they are in control of their investment. They further reveal how the pressure to plan every move with a constant eye on a demonstrable return has supplanted traditional approaches to classroom education and profoundly altered the student experience"--